Acculturation of Aluk Todolo Culture and its Implications for Child Education in Muslim Rural Families - Pasulle, Sonne; Pirol, Abdul; Nawas, M. Zuhri Abu (Al-Hayat: Journal of Islamic Education, 2024)
Aluk Todolo, customary teaching in the rural area of Bastem Utara, constitutes a legacy of a tradition different from Islamic teachings but with values that significantly contribute to children's education in Muslim families. This research uses a qualitative method with a phenomenological approach. The research location is in Dampan Village, North Bastem District, Luwu Regency, South Sulawesi Province. The research subjects involved traditional leaders, Islamic religious leaders, and Muslim families who were selected randomly. Data collection was carried out through observation, in-depth interviews and documentation. Data analysis is done by organizing, interpreting and presenting the data narratively, followed by drawing conclusions. The validity of the data is maintained through the application of source triangulation. The research findings reveal that integrating Aluk Todolo cultural practices in educating Muslim families in Dampan Village fosters moral values and social harmony. Massipa' Namadarana (noble character) and Situtu Nene' (lineage) combine local traditions with religious teachings, strengthen family ties, and promote tolerance. The Rambu Tuka' ceremony (thanksgiving ceremony) displays the unity of culture and religion, enriching the education and life of Muslim families. These findings highlight the importance of integrating local cultural values and religious teachings in building a harmonious, tolerant, inclusive society. This provides insight for policymakers and educational practitioners to adopt educational approaches based on the richness of local culture while promoting universal values of tolerance and cooperation. This study highlights the importance of preserving religious traditions and rituals as an effective tool for promoting diversity and shared understanding in a pluralistic society.